A comparison in attitudes and activity among different groups of private forest owners in Noarootsi municipality, Estonia - Zeigler, Emma (SLU/Southern Swedish Forest Research Centre, 2010)
Noarootsi municipality is situated in north western Estonia and has like the rest of the country had a rather turbulent history of forest ownership. The forest has been mainly privately owned at times and fully state owned during the Soviet Union area. Since the fall of the Soviet Union Estonia has gone through a privatization process in which former land owners could retrieve their farms. Many of the land owners in Noarootsi municipality had fled to Sweden during World War II and did not move back although many did retrieve their properties. The purpose of this study was to research what differences there were between the forest owners living in Estonia and those living in Sweden’s attitudes and behavior regarding forest management and what influenced these. More knowledge about this may give the Estonian forestry sector a greater ability to fulfill the forest owners’ objectives and improve the activity on their properties. Data for the study was collected through a questionnaire that was sent to 145 of Noarootsi municipality’s private forest owners, whereof 70 lived in Estonia and 75 lived in Sweden. In total 60 percent of the forms were returned, of the Estonians 59 percent returned the questionnaire while 61 percent of the Swedes returned it. Forest owners living in Sweden were significantly older than those living in Estonia and also female forest owners were significantly older than male forest owners, however it was only among Estonians that the difference between females and males was significant. Naturally, only Estonians lived permanently on their properties but a greater share of the Estonian men than women lived permanently on their property. Of the survey’s all respondents, a greater proportion were men than women. Estonian forest owners’ ownership objectives were in general more connected to an economically significant use of the forest than the Swedish forest owners’ ownership objectives were. Swedes in general thought family ties were of greatest importance and secondly opportunity of recreation. The Estonians in general instead rated access to timber or firewood of greater importance. Family ties were important among Estonians too, but not much more than the access to residence. Estonians had in general rated most motives of acquiring of greater importance than Swedes. Pursuing forestry was rated approximately as high by both groups, but the importance of pursuing nature conservation was rated higher than forestry by Estonians and lower than forestry by Swedes. Men in general rated all motives of greater importance than women did. Few respondents estimated their initial knowledge to be more than low. Of those who did, more were Estonian and more had acquired their properties through other ways than the land restitution process. Also, those with more initial knowledge seemed to be using or intend to use their forests for more income related reasons than other forest owners did. Women in general estimated their initial knowledge to be lower than men did. Most respondents gained knowledge since they became forest owners but there was a big variation for what knowledge sources they thought most important. Magazines and books were important for the Estonians but not so for the Swedes and this may be due to these sources in part are in Estonian and difficult for Swedes to assimilate. More important for the Swedes and on-property residents were family or friends, which may imply a wider spread forestry tradition among Swedes and those living by their forests. Information evenings and in particular forest days were important sources for cooperative members. Probably the members have better accessibility to these sources through the cooperative. 4 Close to sixty percent of the respondents carried out some sort of forestry measure on their own but differences between the groups were great. Estonians were much more active than Swedes, which is natural, considering the Estonians living so much closer to their properties and men were more active than women. Furthermore, more of the Estonians and men hired external help for forestry measures than Swedes or women did. But the Swedes in general hired help for a greater number of measures than Estonians did, which was much a result of a very great amount of cooperative members showing they hired help for a large number of measures. More than eighty percent felt a need to hire help in the future. There were no great differences between the groups, except for cooperative members feeling a need of help for a greater number of measures than non-members did. Most of the respondents thought active use of the forest was important. Estonians and women in general thought it was more important than Swedes and men did. A greater amount of the cooperative members than the non-members thought active use was important and for these also the cooperative was considered the most important contact that influenced their forest management. Non-member Swedes instead rated family or friends of greatest importance, while Estonians thought the municipality had greatest influence on their forest management. A cooperative membership seem to play an important role for the activity level in the forest. Although members did not carry out the greatest amount of forestry measures on their own, they were the owners of which the greatest amount hired help, and that hired help for the largest number of measures. They also felt the greatest importance of active use and largest need of hiring future help.